Detection Of Some Heavy Metals Residues In The Local Goat Meat In Kirkuk During The Winter And Summer Seasons - Alperkhdri, Adnan Shakor; Abdullah, Mahfhaoth Khalil; Khidhir, Zaid Khalaf (Sulaimani Journal for Pure and Applied Sciences, 2018)
The purpose of these investigating to now the levels of some heavy metals contamination in muscle, liver and kidney meat for Goat in Kirkuk governorate in summer and winter seasons, samples were collected randomly from animals (aged 6-8 months) from three districts of Kirkuk governorate (Downtown, Daquq and Debis) During the January to February (winter season) and July to August months (summer season). There was a significant effect (p≤0.05) of (muscle, liver and kidney) location and season in lead concentrations, the liver in the center of Kirkuk during winter season recorded highest concentration (7.983 ppm ), the lowest concentration (0.983 ppm) was found in muscles of Daquq in Winter. Highest concentration level of cadmium in kidney during summer season from Daquq was recorded (4.430 ppm), and lowers Concentration of cadmium (3.773 ppm) recorded in liver from Debis during winter. For Copper, the liver in the center of Kirkuk during the summer season had the highest concentration (20.734 ppm) and was a significant effect (p≤0.05), while the Liver from the Daquq at winter was recorded lowest concentration (3.773 ppm). For Cobalt, in summer season in Kirkuk, the liver recorded the highest concentration of cobalt (5.926 ppm), while the lowest concentration was recorded in muscle in Winter season from Debis (0.864 ppm). All types of metals recorded levels higher than the internationally accepted limits.
Keywords: Goat; muscle; liver; kidney; heavy metals